EFEKTIVITAS INSTRUMEN ASESMEN MODEL CREATIVE PROBLEM SOLVING PADA PEMBELAJARAN FISIKA TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA - Eka Yuli Sari Asmawati; Undang Rosidin; Abdurrahman Abdurrahman (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
This study aims to describe the effect of using the assessment of students 'critical thinking skills with Creative Problem Solving learning model and to describe the implementation of assessment instruments using Creative Problem Solving learning model can effectively improve students' critical thinking ability. The research design used is One-Group Pretest-Posttest Design. The sample of the study were 32 students selected randomly selected from 7 classes of XI IPA program in SMAN 1 Metro. To test the significant effect of assessment instruments and to determine the effectiveness level of the product, a normalized gain (N-gain) analysis was performed. Based on the result of research, it is found that there is influence of Creative Problem Solving learning model to students 'critical thinking ability and the use of assessment instruments with Creative Problem Solving learning model in effective learning to improve students' critical thinking ability.